PENGGUNAAN MEDIA AUDIO VISUAL UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN IPAS MATERI BAGAIMANA BENTUK INDONESIAKU DI KELAS VSD GMIT KUANINO 1 KOTA KUPANG - Marni Hello, Serli; Maria Masi, Lolang; Y.N Adoe, Treesly (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Thesis by Serli Marni Hello NIM 2101140106 with the title "Use of Animated Video Media to Improve Student Learning Outcomes in the Science Subject of the Material How is My Indonesia Formed in Class V of GMIT Kuanino 1 Elementary School, Kupang City". The formulation of the research problem is: How to improve student learning outcomes on the material how is my Indonesia formed through the use of audiovisual media?. This study aims to improve student learning outcomes on the material how is my Indonesia formed using audiovisual media. This type of research is Classroom Action Research with the following stages: planning, implementation, observation and reflection. The subjects of this study were 10 grade V students with details of 6 male and 4 female students. Data collection techniques were carried out using observation, test and documentation techniques. This study shows that there was an increase in results from cycle I to cycle II. The average value of cycle I was 71.2 with a percentage of completion of 50%. In cycle II, the average value of students increased to 87.6 with a percentage of completion of 90%. Based on the results of the study above, it can be concluded that the use of audiovisual media in learning how my Indonesia looks like can improve student learning outcomes in class V of GMIT Kuanino 1 Elementary School, Kupang City.